2010
DOI: 10.1139/z10-012
|View full text |Cite
|
Sign up to set email alerts
|

Ontogeny of swimming movements in bronze corydoras (Corydoras aeneus)

Abstract: Fish larvae experience fundamental morphological, physiological, and physical changes from hatching to adulthood. All of these changes have an effect on the locomotor movements observed in the larvae. We describe the development of swimming movements in larval bronze corydoras (Corydoras aeneus (Gill, 1858); Ostariophysi, Siluriformes) during their ontogeny. Swimming movements of adults and larvae, aged 0-512 h posthatching, were recorded at 500 frames/s. Movements were analyzed by digitizing points along the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 40 publications
1
8
0
Order By: Relevance
“…Our result, that adipose fins have evolved repeatedly, is based on the phylogenetic hypothesis of Near et al [34] and appears robust relative to minor topological changes among euteleosts [35]. A few analyses have found Characiformes to be paraphyletic, with Siluriformes nested within Characiformes [53,54]. Although our analysis does not include trees of this topology, characiform paraphyly is unlikely to change our result.…”
Section: (A) Adipose Fins Have Evolved Repeatedlysupporting
confidence: 54%
“…Our result, that adipose fins have evolved repeatedly, is based on the phylogenetic hypothesis of Near et al [34] and appears robust relative to minor topological changes among euteleosts [35]. A few analyses have found Characiformes to be paraphyletic, with Siluriformes nested within Characiformes [53,54]. Although our analysis does not include trees of this topology, characiform paraphyly is unlikely to change our result.…”
Section: (A) Adipose Fins Have Evolved Repeatedlysupporting
confidence: 54%
“…) found that lateral excursion of the trunk at the position of the adipose fin did not exceed 1.0 mm [17].…”
mentioning
confidence: 92%
“…The probe, a pinhead, was mounted to the end of a voice coil positioning stage (VCS10-023-BS-01-M, H2 W Technologies Inc., Valencia, CA, USA) and controlled by a programmable driver (Intelligent Servo Drive IDM640-8EI, Technosoft, Canton, MI, USA). Lateral trunk displacement at the position of the adipose fin does not exceed 1.0 mm in C. aeneus [17]; these data were used to estimate a range of behaviourally relevant stimuli. A series of four randomly ordered step-and-hold stimuli (0.12, 0.24, 0.36 and 0.48 mm) of 5 s in duration were applied to the fin to assess the nerve's response to lateral deformation of the fin membrane.…”
mentioning
confidence: 99%
“…Fishes benefit from shoal membership through increased hydrodynamic efficiency, and augmented security and foraging success (Pitcher & Parrish, 1993). Some studies have devoted attention to development of behavior and sensory organs in Siluriformes (KhoDa et al, 1995;Pruzsinszky & laDich,1998;maguit et al, 2010;mukai et al, 2010;rahmah et al, 2011) but we believe this is the first study demonstrating developmental changes in aggregation size and in shoaling behavior in Corydoras aff. paleatus.…”
Section: Discussionmentioning
confidence: 85%